Comparison of Hydrogels Based on Commercial Chitosan and Beetosan(®) Containing Nanosilver - Tyliszczak, Bożena (Molecules, 2016)
Two series of hydrogels on the basis of commercial chitosan and chitosan derived from naturally expired honeybees are presented in this article. Sorption capacity and behavior of both kind of materials in simulated body fluids such as Ringer’s liquid or artificial saliva have been determined and compared. Presence of functional groups in synthesized materials have been determined by means of FT-IR spectroscopy. Structure and homogeneity of their surface have been defined using Scanning Electron Microscopy. Based on the conducted research, it can be stated that both chitosan and Beetosan(®) hydrogels have very similar characteristics. It is worth noting that synthesis of such materials is environmentally friendly and leads to obtaining polymers that can be used for biomedical applications. Tested materials are characterized by low sorption capacity and do not have a negative impact on simulated body fluids. Moreover, based on the cell lines studies, it can be stated that Beetosan(®) hydrogels have a negative influence on cells of cancerous origin and, what is important, significantly less adverse effects on fibroblasts.